Capacity Development of Civil Engineering Alumni and Students in Disaster-Resistant Home Structural Design Efforts - Hendrig Sudradjat; Widha ardhiansyah; Putri Fatmawati (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Indonesia, a country located in the Pacific Ring of Fire, has a high level of vulnerability to earthquakes. This condition demands an increase in the capacity of civil engineering human resources to design safe and disaster-resistant buildings. This study aims to evaluate the effectiveness of project-based learning training with a focus on the application of SNI 1726:2019, structural modeling using ETABS/RSA, lateral load calculations, and the design of simple earthquake-resistant houses. The research method involved final-year civil engineering students and alumni who participated in a series of trainings, with evaluations through pre-tests, post-tests, and design assessments. The results showed an increase in competency in all aspects, especially the understanding of the SNI 1726:2019 standard and lateral load calculations. In addition, participants were able to produce simple house designs that meet the basic criteria for earthquake resistance, material efficiency, and structural stability. These findings indicate that applied training can bridge the gap between academic theory and practical skills needed in the workplace. This research contributes to strengthening the capacity of civil engineering in supporting resilient infrastructure development and has important implications for the integration of similar training into higher education curricula and community service programs.